Case report: Resuscitative endovascular balloon occlusion after iatrogenic injury of the common iliac artery during neurosurgical dorsal lumbar microdiscectomy - Fiedler, Mascha O.; Böckler, Dittmar; Giese, Henrik; Popp, Erik; Schmitt, Felix C. F.; Weigand, Markus A.; Erhart, Philipp (Frontiers in Medicine, 2023)
Introduction and Importance This case report describes resuscitative endovascular balloon occlusion (REBOA) of the aorta in a patient with life-threatening iatrogenic bleeding of the right common iliac artery during elective dorsal lumbar spine surgery. REBOA is an emergency procedure for temporary intra-aortic balloon occlusion being increasingly reported and published since its inauguration in 1954. The interdisciplinary management of hemorrhage and technical notes for successful REBOA procedure will be presented. Case presentation A 53-year-old female patient was admitted to the neurosurgery clinic suffering from left sided L5 radiculopathy. During surgery, the anterior longitudinal ligament was perforated and an arterial vessel was lacerated. The patient became hemodynamically instable demanding prompt supine repositioning and cardiopulmonary resuscitation (CPR). REBOA enabled cardiovascular stabilization after 90 minutes of CPR and laparotomy with vascular reconstruction and contributed to survival of the patient without major clinical deficits. The patient was discharged from the ICU after 7 days. Clinical Discussion Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emergency procedure to control life-threatening hemorrhage. REBOA should be available on-scene and applied by well-trained vascular surgery personal to control vascular complications or extend to emergency laparotomy and thoracotomy with aortic cross-clamping in case of in-hospital non-controllable hemorrhages. In case of ongoing CPR, we recommend surgical groin incision, open puncture of the pulseless common femoral artery and aortic balloon inflation in REBOA zone I. Hereby fast access and CPR optimization for heart and brain perfusion are maintained. Conclusion Training for REBOA is the decisive factor to control selected cases of in-house and in a second step, outpatient massive arterial abdominal bleeding complications.